2019
DOI: 10.17582/journal.aavs/2019/7.6.441.446
|View full text |Cite
|
Sign up to set email alerts
|

TNF-alpha Level, a Marker for Ivermectin Induced Immune Modulation in Cattle with Ocular Squamous Cell Carcinoma (BOSCC)

Abstract: Ivermectin drug used in the treatment of endo and ecto parasites in animals, but in this study was used to treat Bovine ocularsquamous cell carcinoma (BOSCC) at a dose 200 mg /Kg body weight. Forty cattle were used in this study in a period from January 2014 to December 2015. The result of this study was revealed significant increase (P≤0.05) in the mean of total white blood cells count (5.39 ± 1.052) cell/mm 3 before treatment and reach to (6.49 ± 0.422)cell/mm 3 after treatment and the mean of lymphocyte rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…11,26 Carcinomas are nodular, cauliflower-like, hemorrhagic, ulcerative, friable in consistency, easily crumbly and have bad odor due to contamination. 7 In our study, we also observed that tumoral masses were cauliflower-like, nodular, hemorrhagic, ulcerative, and were covered with a purulent discharge similar to that reported in previous literature. 5,13,22,27 The number and intensity of keratin pearls, the width of the tumoral island formation, and pleomorphism are important parameters in determining the BOSCC differentiation degrees.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…11,26 Carcinomas are nodular, cauliflower-like, hemorrhagic, ulcerative, friable in consistency, easily crumbly and have bad odor due to contamination. 7 In our study, we also observed that tumoral masses were cauliflower-like, nodular, hemorrhagic, ulcerative, and were covered with a purulent discharge similar to that reported in previous literature. 5,13,22,27 The number and intensity of keratin pearls, the width of the tumoral island formation, and pleomorphism are important parameters in determining the BOSCC differentiation degrees.…”
Section: Discussionsupporting
confidence: 90%
“…[3][4][5] The tumor is mostly detected in Hereford, Holstein, and Simmental cattle breeds; the incidence is more common in the age of 3 to 7 years; and the tumor has no sex pre-disposition. [6][7][8] BOSCC, which originates from the stratum spinosum cells of stratified squamous epithelium, can occur in different ocular and periocular tissues including the palpebral skin, epithelial surfaces of the cornea and conjunctiva, third eyelid, and limbus. 8,9 The tumor is typically ulcerative, firm, lobular, and has a cauliflower-like appearance, and when seen with purulent panophthalmitis, it can be covered with a mucopurulent exudate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result can be compared with dexamethasone, which also decreases the level of TNF significantly, but there was no significant difference found between the ivermectin and dexamethasone groups. Ivermectin was found to significantly lower TNF levels when compared with the untreated group [52]. Decrease in TNF levels has been linked to a potential protective effect in CFA‐induced arthritis [40].…”
Section: Discussionmentioning
confidence: 99%